An exploration of graduate students’ perceived social presence and media richness of a synchronous videoconferencing learning environment - Wempe, Brandie Colleen (Kansas State University, 2022)
Although online course enrollments have increased over the past two decades (Berry, 2017), low retention rates persist (Muilenburg & Berge, 2005; Ng, 2019) due to students feeling isolated and a lack of social connection with their instructor and classmates (Baxter, 2012; Lowenthal, 2009; Pinsk et al., 2014). High dropout rates have been reported (Muilenburg & Berge, 2005; Ng, 2019; Shelton et al., 2017), with a lack of social presence being a barrier to students engaging in and completing online courses. In April 2020, approximately 43% of the world population was in lockdown due to COVID-19 (Marinoni et al., 2020). Lockdown and social distancing measures immediately affected higher education, which required instructors to switch from teaching face-to-face to an online hybrid style that incorporated synchronous videoconferencing into the course delivery (Skulmowski & Rey, 2020). The communication theories of social presence and media richness were applied to better understand the relationship between the communication medium (videoconferencing) and the interactions within the mediated environments (e.g., Zoom). Looking through the lens of social constructivism, this correlational cross-sectional study explored graduate students’ perceived social presence and media richness of a synchronous videoconferencing learning environment by investigating how strongly and in what direction social presence, social space, sociability, and media richness were related. The Pearson correlation analysis indicated a strong, positive correlation between Social Presence and Social Space (Positive Group Behavior); Social Presence and Sociability; Social Presence and Media Richness; Social Space (Positive Group Behavior) and Sociability; Social Space (Positive Group Behavior) and Media Richness; and Sociability and Media Richness. A moderate, negative correlation was indicated between Social Space (Negative Group Behavior) and Social Presence; Social Space (Negative Group Behavior) and Sociability; and Social Space (Negative Group Behavior) and Media Richness.
Keywords: Synchronous videoconferencing; Media richness; Social presence; Social space; Sociability